2020
DOI: 10.3390/ph13090239
|View full text |Cite
|
Sign up to set email alerts
|

Incubation with a Complex Orange Essential Oil Leads to Evolved Mutants with Increased Resistance and Tolerance

Abstract: Emergence of strains with increased resistance/tolerance to natural antimicrobials was evidenced after cyclic exposure to carvacrol, citral, and (+)-limonene oxide. However, no previous studies have reported the development of resistance and tolerance to complex essential oils (EOs). This study seeks to evaluate the occurrence of Staphylococcus aureus strains resistant and tolerant to a complex orange essential oil (OEO) after prolonged cyclic treatments at low concentrations. Phenotypic characterization of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In comparison to EcWT, EcAEN 10 and EcAEN 20 showed a 25% increase in MIC value against AEN, and EcCOLIFIT 10 and EcCOLIFIT 20 showed an increase in MIC value against COLIFIT of the order of 14.3% and 28.6%, respectively. However, compared to other studies in which RVs have also emerged after exposure to complex EOs [9][10][11], the observed increase in resistance was relatively low. Apart from direct resistance, AEN-and COLIFIT-RVs (EcAEN 10 , EcAEN 20 , EcCOLIFIT 10 , and EcCOLIFIT 20 ) displayed a slight cross-resistance against AEN, COLIFIT, and cinnamaldehyde.…”
Section: Phenotypic Characterization Of Evolved Mutantscontrasting
confidence: 91%
See 2 more Smart Citations
“…In comparison to EcWT, EcAEN 10 and EcAEN 20 showed a 25% increase in MIC value against AEN, and EcCOLIFIT 10 and EcCOLIFIT 20 showed an increase in MIC value against COLIFIT of the order of 14.3% and 28.6%, respectively. However, compared to other studies in which RVs have also emerged after exposure to complex EOs [9][10][11], the observed increase in resistance was relatively low. Apart from direct resistance, AEN-and COLIFIT-RVs (EcAEN 10 , EcAEN 20 , EcCOLIFIT 10 , and EcCOLIFIT 20 ) displayed a slight cross-resistance against AEN, COLIFIT, and cinnamaldehyde.…”
Section: Phenotypic Characterization Of Evolved Mutantscontrasting
confidence: 91%
“…To determine the MIC values of the commercial EOs and the ICs, we adopted the methodology widely agreed upon in previous studies [9][10][11]. We added increasing concentrations of AEN, COLIFIT, thymol, and cinnamaldehyde (50-500 µL/L with 50 µL/L intervals) to test tubes with 5 mL of MHB.…”
Section: Minimum Inhibitory Concentration (Mic) and Minimum Bacterici...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, orange essential oil contains myrcene, sabinene, α-sabinene, linalool, and other compounds in minor amounts (Table 1). The antimicrobial properties of orange essential oil can be assigned to each constituent feature of isolation (Guimarães et al, 2019) and also the synergy that occurs between them (Ambrosio et al, 2019;Berdejo et al, 2020). Ambrosio et al (2019) demonstrated that limonene could collaborate with the selective activity of citrus oils when present in the gut, promoting the beneficial bacteria, while other minor compounds could act to inhibit pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthwhile to highlight the demonstration of the bacteria developing resistance and tolerance towards EOs; however, cross-resistance to antibiotics was not reported [ 137 ]. Treatment of P. aeruginosa infection with a sub-inhibitory concentration of cinnamon bark oil or cinnamaldehyde as an adjunctive therapy may potentially induce expression of efflux pumps, and this needs further investigation to ascertain the use of EOs with any antagonistic effects [ 138 ].…”
Section: Strategies Targeting Antimicrobial-resistant Enzymesmentioning
confidence: 99%